Bridging The Gap Of Information Source And Access To Dialysis Services With Klikdialisis.Com, As An Integrated Digital Communication Platform - Tri Astuti; Satya Aditya Wibowo (Malahayati Nursing Journal, 2022)
ABSTRACTThe diagnosis and management of CKD, incredibly advanced CKD, can have a major impact on the patient's life due to the limitations of daily activities that the patient experiences, whether at work, traveling, or socializing. The author formulates the research design and methodology, as seen in Figure 2.2. In this research, both the external and internal analysis plays an important role in defining the clear gap of dialysis access and barriers and understanding the competitive advantages of klikdialisis.com. KlikDialisis.com is a health application platform based on socioeconomics by connecting patients, especially kidney patients, with dialysis service providers and other kidney health facilities.